Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.4102/jsava.v76i4.424
|View full text |Cite
|
Sign up to set email alerts
|

Reversible anaesthesia of free-ranging lions (Panthera leo) in Zimbabwe

Abstract: The combination of medetomidine-zolazepam-tiletamine with subsequent antagonism by atipamezole was evaluated for reversible anaesthesia of free-ranging lions (Panthera leo). Twenty-one anaesthetic events of 17 free-ranging lions (5 males and 12 females, body weight 105-211 kg) were studied in Zimbabwe. Medetomidine at 0.027-0.055 mg / kg (total dose 4-11 mg) and zolazepam-tiletamine at 0.38-1.32 mg / kg (total dose 50-275 mg) were administered i.m. by dart injection. The doses were gradually decreased to impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
32
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 16 publications
(25 reference statements)
5
32
1
Order By: Relevance
“…This is similar to other studies in lions using α 2 -adrenoceptor agonists. Bradyarrhythmias were noted in several lions and have also been observed in cheetah immobilised with BMM (Gunkel & Lafortune 2007 (Bush et al 1978;Fahlman et al 2005). Lactate values were within normal limits for domestic cats and probably did not contribute to the metabolic acidosis (King 2004).…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…This is similar to other studies in lions using α 2 -adrenoceptor agonists. Bradyarrhythmias were noted in several lions and have also been observed in cheetah immobilised with BMM (Gunkel & Lafortune 2007 (Bush et al 1978;Fahlman et al 2005). Lactate values were within normal limits for domestic cats and probably did not contribute to the metabolic acidosis (King 2004).…”
mentioning
confidence: 90%
“…Stable anaesthesia without a need for additional doses is a major advantage for personnel safety when working with lions. In comparison, other authors using medetomidine-ketamine and tiletamine-zolazepam-medetomidine reported sudden recovery and spontaneous movements requiring further doses of drugs (Fahlman et al 2005;Quandt 2005). Two of the three animals that were excluded from this study due to subcutaneous dart placement and prolonged drug absorption, were initially not administered the antidotes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies involving these animals require chemical restraint, given their unruly behavior in the presence of humans. Therefore, the various chemical immobilization techniques of wild mammals are an invaluable tool in the search of these animals (Hime 1974, Logan et al 1986, Barone et al 1994, Tomizawa et al 1997, Miller et al 2003, Fahlman et al 2005, Jacquier et al 2006, Carpenter & Brunson 2013.…”
Section: Introductionmentioning
confidence: 99%